2021
DOI: 10.3390/jcm10163560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Histological Sample Volumes among Various Endoscopic Ultrasound-Guided Biopsy Needles

Abstract: Endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) enables easy and accurate pathological assessment. Here, we compared and assessed the area of samples on glass slides for three needle types: a 19-gauge Franseen needle (Acquire, Boston Scientific, Natick, MA, USA), a 22-gauge Franseen needle, and a 19-gauge fine-needle aspiration (FNA) needle (EZ Shot 3 Plus; Olympus, Tokyo, Japan). Among patients with suspected pancreatic cancer, with a ≥20 mm tumor located in the pancreatic body and tail, and who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…It has been reported that 19-G Franseen needles can increase the area by approximately three times compared to 22-G needles. 34 There were several limitations in the present study. First, this study had a crossover design, and the endosonographer was not blinded, which could have resulted in operator-related bias.…”
Section: Discussionmentioning
confidence: 84%
“…It has been reported that 19-G Franseen needles can increase the area by approximately three times compared to 22-G needles. 34 There were several limitations in the present study. First, this study had a crossover design, and the endosonographer was not blinded, which could have resulted in operator-related bias.…”
Section: Discussionmentioning
confidence: 84%
“…The recently developed FNB needles could improve the quality and quantity of samples, for example, by using returned side holes or specifically processed tips 21 . Acquire (Boston Scientific Co., Natick, MA, USA), a Franseen‐type FNB needle, was found to collect more tissue section surface areas than the FNA needle 17,18,22 . Although Ikeda et al reported a higher rate of NOP criteria fulfillment with a 22‐G FNB needle than with a 22‐G FNA needle for EUS‐TA (11.4% vs 32.6%, P = 0.033), the results were still unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…21 Acquire (Boston Scientific Co., Natick, MA, USA), a Franseen-type FNB needle, was found to collect more tissue section surface areas than the FNA needle. 17,18,22 Although Ikeda et al reported a higher rate of NOP criteria fulfillment with a 22-G FNB needle than with a 22-G FNA needle for EUS-TA (11.4% vs 32.6%, P = 0.033), the results were still unsatisfactory. Furthermore, the FNB needles used were of different types rather than a single type.…”
Section: Discussionmentioning
confidence: 99%
“…54 Takahashi et al showed superiority of a 19G Franseen needle (Acquire; Boston Scientific) compared with each of a 19G conventional needle (EZ Shot 3 Plus; Olympus, Tokyo, Japan) (P = 0.010) and a 22G Franseen needle (P = 0.008) in histological sample volumes by measuring the areas of core tissue, although the target lesions were restricted to PDAC with a tumor size of ≥20 mm, located in the body or tail of the pancreas. 58 In a recent retrospective study, Park et al evaluated the optimal approach for NGS for PDAC using EUS-FNA samples. They found a yield of only 57.4%, for the reason that the samples were collected without intention for NGS during clinical diagnostic examination, and multivariate analysis revealed a large needle size as independently associated with successful NGS.…”
Section: History and Future Perspective Of Needles And Techniques For...mentioning
confidence: 99%
“…Takahashi et al . showed superiority of a 19G Franseen needle (Acquire; Boston Scientific) compared with each of a 19G conventional needle (EZ Shot 3 Plus; Olympus, Tokyo, Japan) ( P = 0.010) and a 22G Franseen needle ( P = 0.008) in histological sample volumes by measuring the areas of core tissue, although the target lesions were restricted to PDAC with a tumor size of ≥20 mm, located in the body or tail of the pancreas 58 …”
Section: History and Future Perspective Of Needles And Techniques For...mentioning
confidence: 99%